Numerical analysis for the effect of tip clearance in a low specific speed mixed-flow pump - Zhiyi Yu; Wenwu Zhang; Baoshan Zhu; Yongjiang Li (Advances in Mechanical Engineering, 2019)
To study the influence of tip clearance on performance (external characteristics, pressure fluctuation and tip loss) of a low specific speed mixed-flow pump, unsteady simulation was performed for the whole flow passage with five tip clearance sizes ( δ 0  = 0 mm, δ 1  = 0.10 mm, δ 2  = 0.25 mm, δ 3  = 0.75 mm and δ 4  = 1 mm). The reliability of the numerical methodology was verified in external characteristics (efficiency, head and power) and fluctuation. The performance of the pump was obtained under different discharges and tip clearance sizes using ANSYS CFX. The results showed that the variation of tip clearance size has greater effect on the external characteristics under large discharges. Meanwhile, along the flow direction, the fluctuation coefficients near the impeller shroud increase gradually with the smaller tip clearance sizes ( δ  = 0.10 and 0.25 mm), while for the larger tip clearance sizes ( δ  = 0.75 and 1.00 mm), the significant increase of fluctuation near the shroud of impeller inlet is closely associated with the clear leakage vortex and the large region of low pressure. Besides, with the increase of tip clearance size, the effect of tip clearance will become more remarkable under different discharge conditions. According to this study, for the optimization design of such pumps, the size of the tip clearance is suggested to be about 0.9% times the blade height at middle of the impeller passage.